2013
DOI: 10.1002/0471250953.bi1321s41
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and the Analysis of Proteomic Data: 2013 Overview of Current Protein‐Profiling Technologies

Abstract: Mass spectrometry has become a major tool in the study of proteomes. The analysis of proteolytic peptides and their fragment ions by this technique enables the identification and quantitation of the precursor proteins in a mixture. However, deducing chemical structures and then protein sequences from mass‐to‐charge ratios is a challenging computational task. Software tools incorporating powerful algorithms and statistical methods improved our ability to process the large quantities of proteomics data. Reposito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 122 publications
0
15
0
Order By: Relevance
“…Also, a conservative search engine (Protein-Pilot) was applied in our studies, which was reflected by the very low FDR reported. It is known that the choice of search engine influences the detection of proteins (Bruce et al, 2013). Applying a search engine with a low FDR obviously decreases the number of positive hits (Elias and Gygi, 2007).…”
Section: Total Detection Of Proteins By 2d-lc-ms/msmentioning
confidence: 99%
“…Also, a conservative search engine (Protein-Pilot) was applied in our studies, which was reflected by the very low FDR reported. It is known that the choice of search engine influences the detection of proteins (Bruce et al, 2013). Applying a search engine with a low FDR obviously decreases the number of positive hits (Elias and Gygi, 2007).…”
Section: Total Detection Of Proteins By 2d-lc-ms/msmentioning
confidence: 99%
“…Comparison to a proteome database allows the assignment of the tandem mass spectrum to its most likely peptide sequence and, ultimately, parent protein of origin. 11,75,76 Despite successes, glycoproteomics remains challenging for a number of reasons. Glycosylation is a labile PTM and requires technical expertise to ensure that the glycan is preserved in its entirety during sample handling or during MS analysis.…”
Section: Glycosylation Is An Important Ptm That Influences Proteinmentioning
confidence: 99%
“…With recent advances in mass spectrometry technology, a single analysis can contain more than 100,000 tandem mass spectra, and a means to efficiently process the results becomes a necessity (Bruce et al., 2013). STRAP PTM is a software program with the capability to rapidly sift through large amounts of proteomics data in the search for differential PTMs based on spectral counting (Spencer et al, 2013a).…”
Section: Basic Protocolmentioning
confidence: 99%